Shukhrat and folklore: Mental Enlightenment Scientific–Methodological Journal. Volume 2021 [Issue 2] 2021. ISSN: 2181-6131. OAK.UZ. - soatova, nodira (FILOLOGIYA UFQLARI JURNALI, 2022)
Maqola Shuhrat ijodiga bag’ishlangan